2015
DOI: 10.4236/ojmsi.2015.32005
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Presence and Performance in Virtual Simulation Training

Abstract: The use of virtual simulation-based training continues to expand, as organizations explore alternative methods to reduce the cost of training. While virtual simulation has been empirically validated to be effective in the transfer of skills to the live environment, what is still unknown is what effect, if any, that an individual's sense of presence in the simulation has on their performance. In this paper, we examine the relationship between presence and performance while performing a psychomotor task in a vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(86 citation statements)
references
References 24 publications
3
79
3
1
Order By: Relevance
“…While other studies have identified potential mechanisms for HMD-VR transfer by examining existing literature [7], there is inconclusive evidence for why motor skill acquisition in HMD-VR and transfer to other environments may be more effective for some individuals compared to others. The two presence themes identified support previous findings that levels of presence relate to motor performance in an HMD-VR enviorment [46] and extend these findings to the transfer of motor skill acquisition. Additionally, previous experience with the training device, which is HMD-VR in the present case, support findings that the transfer of spatial knowledge is influenced by previous experience with the environment [31].…”
Section: Discussionsupporting
confidence: 84%
“…While other studies have identified potential mechanisms for HMD-VR transfer by examining existing literature [7], there is inconclusive evidence for why motor skill acquisition in HMD-VR and transfer to other environments may be more effective for some individuals compared to others. The two presence themes identified support previous findings that levels of presence relate to motor performance in an HMD-VR enviorment [46] and extend these findings to the transfer of motor skill acquisition. Additionally, previous experience with the training device, which is HMD-VR in the present case, support findings that the transfer of spatial knowledge is influenced by previous experience with the environment [31].…”
Section: Discussionsupporting
confidence: 84%
“…These three studies taken together (Butavicius, Vozzo, Braithwaite, & Galanis, 2012;Seymour, et al, 2002;Stevens & Kincaid, 2015) suggest that at worst, VR training should match the performance that traditional training methods generate, which is in line with the findings of our current study, where we noted no performance differences between the two graphics conditions. This result is promising when validating VR as an alternative to traditional simulator training.…”
Section: Stevens and Kincaidsupporting
confidence: 91%
“…Numerous studies have found that presence is positively related to performance in normal young individuals. In younger adults, larger presence has been associated with better sustained attention (Witmer & Singer, 1998), psychomotor performance (Stevens & Kincaid, 2015;Witmer & Singer, 1994), and spatial memory (Bailey & Witmer, 1994). It was also found that VR conditions that reduce presence, for instance those with limited user-environment interactions or which rely on less natural environments, also have deleterious effects on performance (for a review, see Nash, Edwards, Thompson, & Barfield, 2000).…”
mentioning
confidence: 99%